Unraveling the potential of graphene quantum dots against Mycobacterium tuberculosis infection - Santarelli, Giulia; Perini, Giordano; Salustri, Alessandro; Palucci, Ivana; Rosato, Roberto; Palmieri, Valentina; Iacovelli, Camilla; Bellesi, Silvia; Sali, Michela; Sanguinetti, Maurizio; De Spirito, Marco; Papi, Massimiliano; et al. (Frontiers in Microbiology, 2024)
Introduction The emergence of drug-resistant Mycobacterium tuberculosis (Mtb) strains has underscored the urgent need for novel therapeutic approaches. Carbon-based nanomaterials, such as graphene oxide (GO), have shown potential in anti-TB activities but suffer from significant toxicity issues. Methods This study explores the anti-TB potential of differently functionalized graphene quantum dots (GQDs) – non-functionalized, L-GQDs, aminated (NH2-GQDs), and carboxylated (COOH-GQDs) – alone and in combination with standard TB drugs (isoniazid, amikacin, and linezolid). Their effects were assessed in both axenic cultures and in vitro infection models. Results GQDs alone did not demonstrate direct mycobactericidal effects nor trapping activity. However, the combination of NH2-GQDs with amikacin significantly reduced CFUs in in vitro models. NH2-GQDs and COOH-GQDs also enhanced the antimicrobial activity of amikacin in infected macrophages, although L-GQDs and COOH-GQDs alone showed no significant activity. Discussion The results suggest that specific types of GQDs, particularly NH2-GQDs, can enhance the efficacy of existing anti-TB drugs. These nanoparticles might serve as effective adjuvants in anti-TB therapy by boosting drug performance and reducing bacterial counts in host cells, highlighting their potential as part of advanced drug delivery systems in tuberculosis treatment. Further investigations are needed to better understand their mechanisms and optimize their use in clinical settings.